Enhancing Financial Report Quality in Indonesia Through HR, Standards, and Controls - NURASIK; Setiawan , M. Rizal (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of Human Resources (HR) quality, Government Accounting Standards (SAP) implementation, and Internal Control Systems (SPI) on the financial report quality at the Taman District Office in Sidoarjo Regency. Using a sample of 54 employees and a quantitative approach, data were collected via questionnaires and analyzed with multiple linear regression. Findings show that HR quality, SAP implementation, and SPI significantly influence financial report quality both individually and collectively, with a combined impact of 65.5%. Specifically, HR quality contributes 32%, SAP implementation 36.7%, and SPI 37.3%. To enhance financial report quality, improvements in HR, SAP application, and SPI are recommended. Highlight: HR quality, SAP implementation, and SPI significantly influence financial report quality. Combined impact of these factors on report quality is 65.5%. HR quality, SAP, and SPI contribute 32%, 36.7%, and 37.3%, respectively. Keywoard: Financial reports, Human resources, Government Accounting Standards, Internal Control Systems, Taman District Office